2009
DOI: 10.3133/sir20095086
|View full text |Cite
|
Sign up to set email alerts
|

Chloride in Groundwater and Surface Water in Areas Underlain by the Glacial Aquifer System, Northern United States

Abstract: The U.S. Geological Survey (USGS) is committed to providing the Nation with credible scientific information that helps to enhance and protect the overall quality of life and that facilitates effective management of water, biological, energy, and mineral resources (http://www.usgs.gov/). Information on the Nation's water resources is critical to ensuring long-term availability of water that is safe for drinking and recreation and is suitable for industry, irrigation, and fish and wildlife. Population growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
114
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 23 publications
9
114
1
1
Order By: Relevance
“…We chose to expose developing larvae to elevated chloride upon reaching Gosner stage 25 (Gosner 1960), the point in larval development where tadpoles begin to serve as consumers in the pond food web, which was the focus of this study. Chloride concentrations in urban ponds are not constant but occur in pulses throughout the year (Jackson and Jobbagy 2005;Howard and Maier 2007;Kelly et al 2008;Mullaney et al 2009), therefore frog embryos are likely to develop under fluctuating chloride conditions depending on road salt application rates, proximity to roads, timing of snow melt, groundwater recharge, or evaporative concentration as ponds dry during the spring and summer months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to expose developing larvae to elevated chloride upon reaching Gosner stage 25 (Gosner 1960), the point in larval development where tadpoles begin to serve as consumers in the pond food web, which was the focus of this study. Chloride concentrations in urban ponds are not constant but occur in pulses throughout the year (Jackson and Jobbagy 2005;Howard and Maier 2007;Kelly et al 2008;Mullaney et al 2009), therefore frog embryos are likely to develop under fluctuating chloride conditions depending on road salt application rates, proximity to roads, timing of snow melt, groundwater recharge, or evaporative concentration as ponds dry during the spring and summer months.…”
Section: Discussionmentioning
confidence: 99%
“…While the timing of road deicer application, application rates, and chemical make-up vary by jurisdiction (Transportation Research Board 2004;Mullaney et al 2009), freshwater salinization is becoming a year-round phenomenon due to long-term storage and transport of the dissociated salt ions in groundwater and soils (Jackson and Jobbagy 2005;Howard and Maier 2007;Kelly et al 2008;Mullaney et al 2009). Therefore, freshwater food webs are experiencing increasing exposure to deicing salts.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing chloride concentrations have been found in lakes (Chapra et al, 2009;Novotny and Stefan, 2009), rivers (Robinson et al, 2003;Kauschal et al, 2005), and groundwater (Mullaney et al, 2009;Eyles and Meriano, 2010) across the northern hemisphere, particularly as a result of the application of deicing salts for winter road maintenance (Chapra et al, 2009;Daley et al, 2009;Trowbridge et al, 2010). Road salt application rates in Vermont state highway districts within the Lake Champlain Basin increased during the 1990s but then declined in more recent years (Fig.…”
Section: Introductionmentioning
confidence: 91%
“…Extensive research documents the negative impact of these chemicals on freshwater life (e.g., Whitton 1970;Forstner and Prosi 1979;Munn et al 2006;Vonesh and Kraus 2009), yet more recently road salt deicers have been identified as a rising source of salinization to freshwaters in the United States (Kaushal et al 2005). Freshwater salinization is becoming a year-round phenomenon due to long-term storage and transport of dissociated salt ions (e.g., chloride, sodium, magnesium) in groundwater and soils (Jackson and Jobbagy 2005;Howard and Maier 2007;Kelly et al 2008;Mullaney et al 2009). Concerns of toxicity are closely associated with the chloride ion (Marsalek 2003;Kaushal et al 2005) and a positive relationship has been identified between percent impervious surface cover within a watershed and freshwater chloride concentration (Kaushal et al 2005;Morgan et al 2007).…”
Section: Introductionmentioning
confidence: 99%